Livestock Healthcare and Farmer Contentment: An Exploration of Economic and Social Determinants - Menaka C, B G Kulkarni, Nidhi Saraswat (Revista Electronica de Veterinaria, 2024)
Livestock production is essential to global agriculture, greatly contributing to food safety and regional economies. Sustainable agricultural operations must ensure the health and well-being of animals. This study investigates the complex connection between livestock healthcare and farmer satisfaction, considering the economic and social factors that impact this dynamic association. A growing number of stakeholders are concerned about the effective delivery of minor veterinary treatments due to India's severe workforce deficit in providing animal health care. The study intends to determine farmers' satisfaction with Para-veterinary assistance across four Indian states: Andhra Pradesh, Uttarakhand, Himachal Pradesh, and Assam. The study compared weighted mean values across different states to assess and rank satisfaction with basic veterinarian treatments. Pearson's product-moment correlation study showed some intriguing results. Notably, there was a negative relationship between farmers' education levels and their satisfaction with Para-veterinary treatments. There was a positive relationship between the distance from the veterinarian hospital/dispensary and farmer satisfaction. The satisfaction of farmers with modest veterinary services was shown to be correlated with age and landholding. According to the findings, 55.48 percent of respondents expressed a moderate degree of satisfaction with Para-veterinary solutions, while 45.72 percent of participants expressed a high degree of satisfaction. Furthermore, farmers who were more satisfied with the health of their animals were satisfied with their farming experience overall. Addressing these characteristics is ultimately necessary for fostering ecological livestock farming techniques and improving the overall well-being of livestock and farmers.